Zirconia Materials for Dental Implants: A Literature Review - Qu, Yinying; Liu, Lin (Frontiers in Dental Medicine, 2021)
Titanium is currently the most commonly used material for manufacturing dental implants. However, its potential toxic effects and the gray color have resulted in increasing requests for metal-free treatment options. Zirconia is a type of ceramic materials that has been extensively used in medicine field, such as implant abutments and various joint replacement appliances. Amounts of clinical evaluations have indicated good biocompatibility for zirconia products. Besides, its toothlike color, low affinity for plaque and outstanding mechanical and chemical properties have made it an ideal candidate for dental implants. The aim of this study is to review the laboratory and clinical papers about several kinds of zirconia materials and zirconia surface modification techniques. Although there are plenty of literatures on these topics, most of the researches focused on the mechanical properties of the materials or based on cell and animal experiments. Randomized clinical trials on zirconia materials are still urgently needed to validate their application as dental implants.